"Minority within minority" or a "minority of two majorities": religious education and the making of Christian identity in Israel. Issue 3 (16th April 2022) - Agbaria, Ayman K.; Obeid Shehadeh, Hazar
ABSTRACT: This qualitative article examines the making of a distinct Christian identity through confessional teaching of Christianity. As there had been very little empirical research on teachers of religious education and none on teaching Christianity in Israel, this pioneering paper investigates the teachers' views on their goals and challenges, while analysing how Christian identity is constructed, reworked and negotiated in their practice. In doing so, the article reflects on the meaning and implications of two moods of being a Christian in Israel: being a member of a Christian minority within the Arab minority in Israel (minority within minority), and being a member of a Christian minority of the Muslim and the Jewish majorities in Israel (minority of two majorities). The article examines how teachers educate for both moods and ponders over the sociopolitical interests served by the teachers in religious education.